Nanoformulations of Herbal Extracts in Treatment of Neurodegenerative Disorders - Moradi, Seyed Zachariah; Momtaz, Saeideh; Bayrami, Zahra; Farzaei, Mohammad Hosein; Abdollahi, Mohammad (Frontiers in Bioengineering and Biotechnology, 2020)
Nanotechnology is one of the methods that influenced human life in different ways and is a substantial approach that assists to overcome the multiple limitations of various diseases, particularly neurodegenerative disorders (NDs). Diverse nanostructures such as polymer nanoparticles, lipid nanoparticles, nanoliposomes, nano-micelles, and carbon nanotubes (CNTs); as well as different vehicle systems including poly lactic-co-glycolic acid, lactoferrin, and polybutylcyanoacrylate could significantly increase the effectiveness, reduce the side effects, enhance the stability, and improve the pharmacokinetics of many drugs. NDs belong to a group of annoying and debilitating diseases that involve millions of people worldwide. Previous studies revealed that several nanoformulations from a number of natural products such as curcumin (Cur), quercetin (QC), resveratrol (RSV), piperine (PIP), Ginkgo biloba, and Nigella sativa significantly improved the condition of patients diagnosed with NDs. Drug delivery to the central nervous system (CNS) has several limitations, in which the blood brain barrier (BBB) is the main drawback for treatment of NDs. This review discusses the effects of herbal-based nanoformulations, their advantages and disadvantages, to manage NDs. In summary, we conclude that herbal-based nano systems have promising proficiency in treatment of NDs, either alone or in combination with other drugs.